Black Hole Attack in Delay Tolerant Networks: A Survey - Jain, Shikha (International Journal of Computer Sciences and Engineering, 2014)
Delay-Tolerant Network is a network above networks having unique characteristics like intermittent connectivity, longer delays and constraints on resources. DTN have the capability to survive long delays to achieve interoperability between the regional networks. Since nodes are intermittently connected with each other some new future prediction based routing protocols like Prophet, MaxProp have been proposed in this emerging areas for communication purposes. These future prediction based routing protocols depends on some easily modifiable metrics; attackers can easily forge these parameters to attack the network. This paper discusses one such popular Black-Hole attack on these routing protocols and some of the proposed solutions to mitigate their effect in the network.